Religiosity Value as Indonesian Nationalism (Study of Nahdlatul Ulama Multipurpose Ansor Brigade) (Research, Society and Development, 2019)
The religious nationalism of Multipurpose Ansor Brigade (Banser) was made of a series of Indonesian long history. The resolution of Jihad was the momentums that awaken and infused the passion of nationalism among students. The value that became the basic point was derived from Ahlussunnah wal jama’ah annahdliyah teachings which inherited by Baser. This study aimed to describe the religiosity value as the root of nationalism in Indonesia. The methodology used was qualitative methodology with historical approach. The data were collected through historical sources. The result showed that nationalism was influenced by religiosity value. Various training and experience had influence the level of Banser’s religious nationalism. Banser could obtain more experiences through the length of their participation. Therefore, both training and experience could define the level of religiosity and nationalism.